Transit timing variation and transmission spectroscopy analyses of the hot Neptune GJ3470b - S. Awiphan (2018)
© 2016, Published by Oxford University Press on behalf of the Royal Astronomical Society. GJ3470b is a hot Neptune exoplanet orbiting an M dwarf and the first sub-Jovian planet to exhibit Rayleigh scattering. We present transit timing variation (TTV) and transmission spectroscopy analyses of multiwavelength optical photometry from 2.4-m and 0.5-m telescopes at the Thai National Observatory, and the 0.6-m PROMPT-8 telescope in Chile. Our TTV analysis allows us to place an upper mass limit for a second planet in the system. The presence of a hot Jupiter with a period of less than 10 d or a planet with an orbital period between 2.5 and 4.0 d are excluded. Combined optical and near-infrared transmission spectroscopy favour an H/He-dominated haze (mean molecular weight 1.08 ± 0.20) with high particle abundance at high altitude. We also argue that previous near-infrared data favour the presence of methane in the atmosphere of GJ3470b.